Faktor-faktor yang Mempengaruhi Turnover Intention Karyawan di PT Colamas Indah Sejati - Rahman Rahman; Wasiman Wasiman (J-MAS (Jurnal Manajemen dan Sains), 2023)
Turnover intention is the tendency or intention of employees to stop working from their jobs. "Factors that influence turnover intention are the work environment, work motivation and workload. The superiors of PT Colamas Indah Sejati are still not paying enough attention to the work environment, both in the office and in the operational section. beyond the responsibility of the employee. In this study the population used 110 samples with the variables being work environment (X1) motivation (X2), workload (X3) and turnover intention (Y). "In this study the analytical method used was linear regression analysis, to test the truth of the final hypothesis which has been determined by the researchers." Hypothesis testing was carried out by F and T tests, "The results show that the work environment partially has a significant effect on turnover intention, motivation partially has a significant effect on turnover intention and partial workload has a significant effect on turnover intention Work environment (X1), work motivation (X2) and workload (X3) have a positive influence on turnover intention (Y) PT Colamas Indah Sejati